The Need for Special Resolution Regimes for Financial Institutions-The Case of the European Union - Cihak, Martin (IMF Working Papers; Working Paper ;, 2009)
The global financial crisis has demonstrated weaknesses in resolution regimes for financial institutions around the globe, including in the European Union (EU). This paper considers the principles underlying resolution regimes for financial institutions, and draws out how a well-designed resolution regime can expand the toolset available for crisis management. Introducing, or in some cases expanding the scope, of these regimes is pressing to achieve more effective responses to ongoing financial sector weaknesses across the EU.